Echocardiographic and clinical outcomes of MitraClip therapy in patients with severe mitral regurgitation. (25th November 2020) - Rashi, Y; Turyan Medvedovsky, A; Tonchev, I; Perez, A; Elioz, R; Lotan, C; Gilon, D; Planer, D; Danenberg, H.D; Beeri, R; Shuvy, M
Abstract: Background: MitraClip implantation improves mitral regurgitation (MR), however its impact on pulmonary hypertension (PHT) is not fully elucidated. Our hypothesis was that changes in pulmonary pressure after MitraClip implantation might predict outcomes. Methods: We studied a cohort of 149 consecutive patients who underwent MitraClip implantation between August 2015 and September 2019. We compared echocardiographic and clinical variables between a group with not-severe PHT and a group with severe PHT according to Pulmonary artery systolic pressure (PASP) >55 mmHg. Results: Mean age of the cohort was 73±10 years, 75% were men, and 80% had functional MR. There are no differences in baseline characteristics between the two groups. There was a significant reduction of 13.6 mmHg in PASP at the severe PHT group from 68.2±10.9 mmHg before the procedure to 54.6±14.9 after (P=0.001) compared to the absence of a significant change in the second group. This reduction was maintained in the 6 months follow-up. Although PHT is considered a poor prognostic measure, and the severe PHT group had a baseline PASP higher than the not-severe group (P<0.001), however the Kaplan Meier curve did not show any significant difference in overall survival (p=0.468), and there is also no difference in one-year survival. Conclusions: MitraClip therapy improves PASP in patients with severe MR and severe PHT. These patients showed the same survival as patients with not-severe PHT. MitraClip is a safety and effective procedure even for patients with severe PHT, that should not be excluded. Funding Acknowledgement: Type of funding source: None